Bloodborne Pathogens -- OSHA Standard 1910.1030 - Carol J. Lehtola; Charles M. Brown (EDIS)
Revised! ABE-214, a 17-page illustrated fact sheet by Carol J. Lehtola and Charles M. Brown, highlights the information and requirements in OSHA standard 1910.1030, which guides employers in providing for their workers safe and appropriate means for using needles and other devices for drawing and transferring blood and other similar materials. Includes references. Published by the UF Department of Agricultural and Biological Engineering, November 2008.